2014
DOI: 10.1124/jpet.114.214254
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Actions of 11,12-Epoxyeicosatrienoic Acid in Endothelial Cells Are Specific to theR/S-Enantiomer and Require the GsProtein

Abstract: Cytochrome P450-derived epoxides of arachidonic acid [i.e., the epoxyeicosatrienoic acids (EETs)] are important lipid signaling molecules involved in the regulation of vascular tone and angiogenesis. Because many actions of 11,12-cis-epoxyeicosatrienoic acid (EET) are dependent on the activation of protein kinase A (PKA), the existence of a cell-surface G s -coupled receptor has been postulated. To assess whether the responses of endothelial cells to 11,12-EET are enantiomer specific and linked to a potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 52 publications
0
39
0
Order By: Relevance
“…EETs have diverse biological actions including vasodilation, inhibition of inflammation, promoting angiogenesis and organ protection (5,6,10,18). These actions and the cellular components to these actions occur over a wide concentration range from 10 -9 -10 -5 M (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EETs have diverse biological actions including vasodilation, inhibition of inflammation, promoting angiogenesis and organ protection (5,6,10,18). These actions and the cellular components to these actions occur over a wide concentration range from 10 -9 -10 -5 M (4).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, 11,12-and 14,15-EETs inhibit smooth muscle cell migration and aromatase expression (8,9). On endothelial cells, 11,12-EET promotes cell growth, decrease apoptosis, migration, tube formation and angiogenesis, increases tissue plasminogen activator (tPA) release, increases cyclooxygenase-2 (COX-2) expression and alters connexin-43 (Cx43) expression and gap junctions (10)(11)(12)(13)(14)(15)(16)(17). EET isomers also inhibit platelet adhesion to the endothelium, and 11,12-and 8,9-EETs inhibit inflammation by decreasing leukocyte adhesion to the endothelium (18,19).…”
mentioning
confidence: 99%
“…This concept is supported by the fact that there are also differences in responsiveness to different EET stereoisomers and not just the regioisomers. For example, 11(R),12(S)-EET is a more potent activator of renal artery K Ca channels (Zou et al, 1996) and rat airway electrical parameters 1114 Fleming (Pascual et al, 1998), as well as endothelial cell TRP channel translocation and angiogenesis (Ding et al, 2014), than 11(S),12(R)-EET. However, this is not a universal observation because 11(S),12(R)-EET is reportedly more effective than 11(R),12(S)-EET in activating cardiac K ATP channels (Lu et al, 2002).…”
Section: Membrane Epoxyeicosatrienoic Acid Receptorsmentioning
confidence: 99%
“…found that RuR completely overturned smooth muscle hyperpolarization induced by 11, 12‐EET in arteries from WT mice. Ding et al 41. reported that in the endothelial cell membrane, a G(s)‐coupled receptor responds to 11(R),12(S)‐EET and mediates the PKA‐dependent translocation and stimulation of TRPC6 channels.…”
Section: Discussionmentioning
confidence: 99%